Examining Students' Test Anxiety at Yogyakarta State University - Dwiki Rahardian; Nur Hidayanto P.S.P (Universitas Negeri Yogyakarta, 2023)
The current research has general aims to examine the anxiety level of students based on their gender and proficiency concerning English proficiency test at Yogyakarta State University. More specifically, this research tries to discover whether or not there is a significant differences in test anxiety levels between students' gender and proficiency score and to seek the interaction between these two variables on test anxiety. This study employed quantitative method by using survey research design. A sample of 229 students (64 males and 165 females) was subjected to Test Anxiety Inventory questionnaire from Spielberger (1980). Then, the data were analysed by using descriptive and inferential statistical analysis. As a way to find out the significant differences and interaction in students gender and proficiency on test anxiety, Two Way Anova was applied as hypothesis testing tools.